PREVALENCE OF OROFACIAL PAIN: CONSISTENT GENDER PREDOMINANCE AND AGE-RELATED VARIATIONS ACROSS STUDIES - Kalanov A.B.; Abdukadirov E.I.; Inoyatova S.O.; Abdullayeva M.B.; Tairova D.Z. (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Background: Orofacial pain, including temporomandibular disorders (TMD), represents a major chronic pain condition with significant impacts on quality of life. This narrative synthesis reviews contemporary epidemiological evidence on the prevalence of orofacial pain and TMD, focusing on gender and age variations.